La educomunicación en la formación de los jóvenes en base al modelo salesiano (sistema preventivo) a través de la radio escolar en el Colegio Domingo Savio en Haití. - St Surin, Judith (2014)
The educomunicación is a concrete modal of an education for the communication, that is to say that it inserts to the new technologies and media programs to the classrooms, as an alternative instrument that develops the critical and conscious capacity of the students in the process of their learning. To join the education and the communication with the aim to achieve that the students are responsible and participative, with critical capacity, capable of questioning the messages that emit the mass media is the intention of the educomunicación. Haiti is a developing country, who has to enter this new millennium with all the capacities and expiring with all the requirements of the time. Nevertheless, the basic thing to reach such a goal is to have formed well people, people with an intellectual, social baggage, spiritual sufficiently to turn reality the dream of seeing, a Haiti developed and proud to it be.